Aspects of nitrogen and mineral nutrition in Icelandic reindeer, Rangifer tarandus - Chase, Leah A.; Studier, Eugene H.; Thorisson, Skarphedinn (Comparative Biochemistry and Physiology Part A: Physiology, 1994)
Nitrogen and mineral (Fe, Mg, Na, K, and Ca) compositions of foodstuffs consumed by and dung produced by male, pregnant and lactating female adult Icelandic reindeer and calves were determined during May of 1992. Iron levels in foodstuffs are consistently above the reported toxicity level for similar-sized sheep (0.5 ppt) and may lead to iron toxicity when consumed by reindeer during periods of high lean body mass catabolism. Male and female reindeer meet nutrient requirements for all measured elements and nitrogen with the possible exception of calcium for males during antler growth. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/31343/1/0000253.pdf